Ononin Shows Anticancer Activity Against Laryngeal Cancer via the Inhibition of ERK/JNK/p38 Signaling Pathway - Ye, Ben; Ma, Jianhua; Li, Zhaoxia; Li, Yang; Han, Xiaopan (Frontiers in Oncology, 2022)
Background Laryngeal cancer is a type of head and neck tumor with a poor prognosis and survival rate. The new cases of laryngeal cancer increased rapidly with a higher mortality rate around the world. Objective The current research work was focused to unveil the in vitro antitumor effects of ononin against the laryngeal cancer Hep-2 cells. Methodology The cytotoxic effects of ononin against the laryngeal cancer Hep-2 cells and normal HuLa-PC laryngeal cells were studied using an 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay. The intracellular Reactive Oxygen Species (ROS) generation, apoptotic cell death, Mitochondrial Membrane Potential (MMP), and cell adhesion on the 25 and 50 µM ononin-treated Hep-2 cells were detected using respective staining assays. The levels of TBARS and antioxidants were assayed using specific kits. The expressions of c-Jun N-terminal kinase 1/2 (JNK1/2), Extracellular Signal-regulated Kinase 1/2 (ERK1/2), p38, Phosphatidylinositol-3 Kinase 1/2 (PI3K1/2), and protein kinase-B (Akt) in the ononin-treated Hep-2 cells were investigated using Reverse Transcription-Polymerase Chain Reaction (RT-PCR) assay. Results The ononin treatment effectively inhibited the Hep-2 cell viability but did not affect the viability of HuLa-PC cells. Furthermore, the ononin treatment effectively improved the intracellular ROS accumulation, depleted the MMP, and triggered apoptosis in Hep-2 cells. The Thiobarbituric acid reactive substances (TBARS) were improved, and Glutathione (GSH) levels and Superoxide dismutase (SOD) were depleted in the ononin-administered Hep-2 cells. The ononin treatment substantially inhibited the JNK/ERK/p38 axis in the Hep-2 cells. Conclusion Together, the outcomes of this exploration proved that the ononin has remarkable antitumor activity against laryngeal cancer Hep-2 cells.